2006
DOI: 10.1161/circulationaha.105.001388
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C Isoform Activation and Endothelin-1 Mediated Defects in Myocyte Contractility After Cardioplegic Arrest and Reperfusion

Abstract: Background-Endothelin-1 (ET-1) is released after hyperkalemic cardioplegic arrest (CA) and reperfusion and may contribute to contractile dysfunction. ET-1 receptor transduction causes activation of protein kinase C (PKC) isoforms, which can cause differential intracellular events. The goal of this study was to determine which PKC isoforms contribute to myocyte contractile dysfunction with ET-1 and CA. Methods and Results-Percent shortening (PERSHORT) and the time to 50% relaxation (T50) were measured in porcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…In the present study, it is demonstrated that levels of PKC-ε are reduced significantly in the I/R myocardium. These new data along with previous data suggest that differential expression/inhibition of PKC isoforms contributes to myocardial function (26,49).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In the present study, it is demonstrated that levels of PKC-ε are reduced significantly in the I/R myocardium. These new data along with previous data suggest that differential expression/inhibition of PKC isoforms contributes to myocardial function (26,49).…”
Section: Discussionsupporting
confidence: 78%
“…For example, in the classical PKC subfamily, total PKC-␤II levels were increased in both remote and I/R myocardium, whereas PKC-␥ was reduced significantly. Past studies have demonstrated that inhibition of PKC-␤II improved contractility in isolated myocytes that have undergone cold cardioplegic arrest and reperfusion with and without the addition of ET (26). Multiple studies have shown the protective effects of PKC-ε activation in the ischemic myocardium (12,48).…”
Section: Discussionmentioning
confidence: 99%
“…Because the calcium relaxation process is not monoexponential, only the latter half of the calcium signal decay could be fitted exponentially to derive the decay constant. Typically, both 50% relaxation decay time (T50) and the decay constant are used to characterize calcium relaxation kinetics (12,29,47,48,57,58,64,72,75,80). Specifically, the Ca 2ϩ relaxation time from the calcium transient peak value to 50% relaxation (T50) was calculated to define the calcium reuptake phase, and Ca 2ϩ decay constant was calculated using an exponential curve fitting program from the 50% calcium peak value to full relaxation.…”
Section: H562 Calcium and Sheet Dysfunction In MDX Heartsmentioning
confidence: 99%
“…Endothelin-1 alone has been shown to activate PKC and reduce cardiomyocyte contractility during periods of ischemia and reperfusion. 32 Importantly, previous research has shown significant increases in endothelin-1 release in the myocardium and peripheral blood following CP/CPB. 33 , 34 We have demonstrated previously that CP/CPB leads to activation of PKC alpha and beta in human coronary microvessels without the presence of endothelin-1.…”
Section: Discussionmentioning
confidence: 99%